Effects of the Tumor‐Vasculature‐Disrupting Agent Verubulin and Two Heteroaryl Analogues on Cancer Cells, Endothelial Cells, and Blood Vessels. Issue 4 (23rd February 2014) - Mahal, Katharina; Resch, Marcus; Ficner, Ralf; Schobert, Rainer; Biersack, Bernhard; Mueller, Thomas
Abstract Two analogues of the discontinued tumor vascular‐disrupting agent verubulin (Azixa®, MPC‐6827, 1) featuring benzo‐1, 4‐dioxan‐6‐yl (compound 5 a) and N‐methylindol‐5‐yl (compound 10) residues instead of the para‐anisyl group on the 4‐(methylamino)‐2‐methylquinazoline pharmacophore, were prepared and found to exceed the antitumor efficacy of the lead compound. They were antiproliferative with single‐digit nanomolar IC50 values against a panel of nine tumor cell lines, while not affecting nonmalignant fibroblasts. Indole 10 surpassed verubulin in seven tumor cell lines including colon, breast, ovarian, and germ cell cancer cell lines. In line with docking studies indicating that compound 10 may bind the colchicine binding site of tubulin more tightly (Ebind=−9.8 kcal mol−1) than verubulin (Ebind=−8.3 kcal mol−1), 10 suppressed the formation of vessel‐like tubes in endothelial cells and destroyed the blood vessels in the chorioallantoic membrane of fertilized chicken eggs at nanomolar concentrations. When applied to nude mice bearing a highly vascularized 1411HP germ cell xenograft tumor, compound 10 displayed pronounced vascular‐disrupting effects that led to hemorrhages and extensive central necrosis in the tumor.